PENGEMBANGAN DAN EVALUASI PROGRAM KONSELING GIZI INTENSIF PADA IBU HAMIL DALAM MENINGKATKAN KUALITAS DIET - Natalia Rorrong Pamilangan; Aminuddin Aminuddin; Agussalim Bukhari; Veni Hadju; Nilawati Usman Andi; Suryani As’ad (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
The quality of a pregnant woman's diet is important for maternal health, fetal growth and development. Nutritional counseling interventions are effective in preventing complications for both mother and fetus. This study aims to determine differences in the quality of the diet of pregnant women in the treatment group and the control group, knowing the difference in the quality of the diet of pregnant women before and after intensive nutrition counseling using leaflet media. This research is a quasi-experimental study with a one post pre control group design approach. This research was conducted at Polongbangkeng Utara Health Center, Takalar Regency. The sampling technique uses simple random sampling method. The sample in this study was pregnant women trimester I-III who met the inclusion and exclusion criteria. The group that received intensive nutrition counseling was 35 people and the group without intensive nutrition counseling was 35 people. Intensive nutritional counseling was provided by researchers with the help of media leaflets then mentoring with a target of six sessions / meetings for 45 minutes. Every 7 (seven) days will be assessed again the quality of the diet per individual Respondents record the food consumed in URT (Household Size) or gram, then researchers estimate / estimate URT (estimated food record) into a measure of weight (grams). The calculation of diet quality is calculated using Nutrisurvey 2007 software. The results showed there were differences in the quality of the diets of pregnant women in the treatment and control groups with a p value = 0.002 <0.05. The results of statistical tests using Wilcoxon indicate there are differences in the quality of the diet of pregnant women before and after intensive nutrition counseling is given (p <0.05). Intensive nutritional counseling using leaflet media can improve the quality of the diet of pregnant women.